Uso de microalgas com potencial para produção de biodiesel e mitigação de impactos ambientais - Sassi , Patrícia Giulianna Petraglia (2016)
Microalgae have been the focus of great interest for the biofuels production due to its enormous capacity to produce biomass, and because many species produce fatty acids in amounts many times the various oleaginous plants. Many microalgae also act as efficient bioremediators domestic and industrial residues, so integrated cultivation of promising microalgae for biofuels coupled to wastewater treatment systems can provide several benefits including cost reductions in effluents treatment and biomass microalgal production, cheapening the culture, promoting nutrient removal and minimizing environmental impacts. This research aimed to evaluate the effectiveness of regional microalgae act in the bioremediation of three types of effluents: biodiesel washing water, shrimp wastewater and agricultural drainage water using potentially promising species for the production of biodiesel that can grow in these effluents as a culture medium . Were used 12 isolated species of microalgae various aquatic environments in northeastern Brazil with 11 freshwater and 1 marine. The selection of species was made considering those which produce substantial amounts of fatty acids, with some even superior to soy. The experiments were performed in chambre culture (25 ± 1 ° C, photoperiod of 12h) in balloons 6L capacity with continuous aeration. The growth of the species under the conditions tested was accompanied by cell counts and measurement of fluorescence in vivo and the physiological responses by flow cytometry. In the effluent were determined NO3, NO2, PO4, pH, COD, turbidity, electrical conductivity and total solids using analytical procedures and/or multiparameter probe. In biodiesel washing water 11 species were tested, only two of which showed good growth. Of these, Monoraphidium contortum was selected for the bioremediation tests due to its higher capacity for growth and be the second species with a higher content of fatty acids. It was found that the species reduces the concentration of NO3, PO4, and COD in percentages of 25.8%, 7.2% and 31.2%, respectively. In shrimp farming water the genus Amphora sp. it showed considerable growth, but lower than the control, but with higher production lipids. Removal PO4, NO3 and NO2 in this species in this effluent was 73.357%, 72.572% and 66.667%, respectively. In agricultural drainage water were tested of which 11 species. Monoraphidium contortum was selected for the bioremediation test and biomass production and yield of the final number of cells in this experimental condition were lower than the control. In this kind effluent removed approximately 73% and 100% for respectively NO3 and PO4. Comparisons of physiological responses showed cell concentrations, florescence chlorophyll and activity of higher esterase in control and increased production of lipids in the drainage water The data show it is possible to use these effluents in the cultivation of microalgae important for biodiesel production with effective reduction of nutrients present in wastewater and that, depending on the species, the effluent may offer favorable conditions for increased production of lipids. However, microalgal cultures in these effluents can be double interest: to minimize environmental impact and producing microalgal biomass that can be used to produce biodiesel, or other byproducts of interest to the biotechnology, thereby reducing production costs in mass culture.